Species Specificity of In Vitro Escherichia coli Adherence to Host Intestinal Cell Membranes and Its Correlation with In Vitro Colonization and Infectivity - Cheney, Christopher P. (1980)
We have previously described an in vitro assay for examining the mucosal adherence of a rabbit diarrheagenic Escherichia coli, RDEC-1. That assay defined the in vitro characteristics of RDEC-1 adherence to brush borders isolated from rabbit ileal epithelial cells. The present study was conducted to examine the species specificity of both in vitro RDEC-1 adherence and in vivo infectivity of RDEC-1 and to compare these specificities. Species specificity in vitro adherence was examined by using brush borders prepared from intestinal epithelial cells of rats, guinea pigs, and rabbits, as well as from a surgically resected specimen of human ileum. Strain RDEC-1 adherence to rabbit brush borders in vitro was significantly greater (P < 0.001) than its adherence to brush borders from any of the other species. Regional specificity of in vitro adherence of RDEC-1 to ileal segments of rabbit intestinal mucosa was also demonstrated. There was significantly greater adherence of RDEC-1 to rabbit ileal brush borders as compared to rabbit jejunal brush borders (P < 0.05). In vivo infectivity was assessed by inoculating RDEC-1 into rats, guinea pigs, and rabbits. RDEC-1 elicited diarrhea in all inoculated rabbits with the mean onset of illness occurring 5 days after inoculation. In contrast, none of the RDEC-1-inoculated rats or guinea pigs developed diarrhea. Furthermore, colonization studies in these animals revealed that RDEC-1 heavily colonized the ileum and cecum (10(9) RDEC-1 colony-forming units/g of tissue) of rabbits; however, only minimal colonization was observed in guinea pigs and rats. In conclusion, the correlation between in vitro adherence and in vivo infectivity that we have observed suggests that the presence of receptors, specific for bacteria, on the surface of the host intestinal mucosa determines species susceptibility to enteric colonization and infectivity by certain strains of enteropathogenic E. coli.